CIVIC CHARACTER SOCIAL RELATIONS TOWARDS A STRONG NATIONAL UNITY BASED ON BROTHERHOOD - Akhyar, Zainul; Elmy, Muhammad; Kiptiah, Mariatul; Huda, Nurul; Hiliadi, Wardiani (International Conference On Social Science Education, 2024)
Social relations between citizens need to be developed to the level of "friendship between citizens" or, with another proverb, "brotherly relations" among humans, and brotherhood among citizens. At the governmental level, the basic principle of the formation of friendly relations and brotherhood among citizens must start from the state's legal policies that are fair to all citizens without discriminating against ethnic groups, sects and population groups in all fields of life; then strengthened and encouraged by the example of "goodness" from community leaders and national leaders. Furthermore, at the level of citizen life, the principle of mutual respect between fellow citizens is also an important part of the life of a pluralistic society; and most importantly, each citizen develops an "attitude of doing good things", and it is done to everyone despite different ethnicities, sects and population groups. Social relations between citizens based on togetherness, friendship and maintaining unity among the diversity of tribes, sects and population groups is a fundamental value recommended by the Pancasila philosophy, which in one of its syllables emphasizes "Indonesian Unity", meaning that the Indonesian nation, which has different backgrounds and conditions of its citizens, must unite as a nation, because this unity will encourage the achievement of the goals of life.